2009
DOI: 10.1111/j.1365-2265.2009.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of impaired fasting glucose in GH‐deficient adults receiving GH replacement compared with untreated subjects

Abstract: Initiation of GH replacement in GHD adults was associated with a mild increase in FPG that often normalized spontaneously. Nevertheless, clinicians should monitor FPG in patients receiving GH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…A total of 28 of the 41 patients presented dysglycaemia at any time during follow-up, and four patients developed DM during GHR. This increment agrees with the values reported in previous studies, 7,12,15 ranging from 0 to 10.2%; this variability could partly be due to ethnic characteristics, genetic predisposition and baseline dysglycaemia, as well as the remarkable obesity of the recruited patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A total of 28 of the 41 patients presented dysglycaemia at any time during follow-up, and four patients developed DM during GHR. This increment agrees with the values reported in previous studies, 7,12,15 ranging from 0 to 10.2%; this variability could partly be due to ethnic characteristics, genetic predisposition and baseline dysglycaemia, as well as the remarkable obesity of the recruited patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, less than half of the subjects had an HbA 1c value recorded at any time during the study. 12 In our patients, BFM remained similar to the baseline level during the 3 years of GHR, which could possibly be an effect of normal ageing of the patients or an unexpected evolution of body composition during follow-up. Several studies have demonstrated that GHR therapy normalises the alterations in body composition through a reduction in BFM and an increase in lean mass, within the first year of treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Initially, there was concern that GH replacement would increase this prevalence further by increasing insulin resistance and hence diabetes rates. Although in the short term fasting plasma glucose may rise on commencing GH replacement (53), improvements in LBM and WHR offset these changes and in the longterm there is no rise in HbA1c (51,52) or plasma glucose (54). After 1 year of GH replacement, normalisation of insulin sensitivity and plasma glucose diurnal variation are seen (55).…”
Section: Other Cardiovascular Risk Factorsmentioning
confidence: 97%
“…Mild and often transient changes in glucose metabolism have been demonstrated to be associated with GH replacement therapy in adults with GHD when compared with untreated adults with GHD (52).…”
Section: Obesitymentioning
confidence: 99%